Strong Photocurrent Response of Selenoarsenates With Different Transition Metal Complexes as Structure-Directing Agents - Tian, Xinyu; Teri, Gele; Shele, Muge; E, Namila; Qi, Liming; Liu, Min; Baiyin, Menghe (Frontiers in Chemistry, 2022)
Four selenoarsenates with different transition-metal complexes [Co(tren)2H]AsSe4 (tren=tris(2-aminoethyl)amine) (1); [Ni2(dien)4][As2Se5] (dien=diethylenetriamine) (2); [Zn(tren)]2[As2Se5] (3) and [Mn(tren)]2[As2Se5] (4) were solvothermally synthesized in a mixed solvent of organic amine and alcohol solution. The compounds 1-4 have pyramidal/tetrahedral structures (AsSe3/AsSe4), and contain transition metal (Co2+, Ni2+, Zn2+ and Mn2+) complex that form distinct zero-dimensional (0-D) clusters. Arsenic atoms form a tetrahedron in compounds 1 and 2; 1 consists of discrete tetrahedral [AsSe4] and transition metal complex [Co(tren)2]2+; 2 is composed of an anion [As2Se5]4- cluster and transition metal complex [Ni(dien)2]2+. In compounds 3 and 4, arsenic atom forms a pyramidal AsSe3 and the two pyramidal AsSe3 share a corner connection to form a dimer [As2Se5]4-; 3 is characterized as a cluster consisting of two [Zn(tren)]Se linked by a dimer [As2Se5]4- linkage; in 4, [Mn(tren)]2Se2 cluster is linked to two trigonal-bipyramidal [Mn(tren)]Se via dimer [As2Se5]4- to form [Mn(tren)]4[As4Se10] cluster. To our knowledge, [Zn(tren)]2[As2Se5] (3) is the first zinc selenoarsenate containing the [As2Se5]4- anion type. Furthermore, the Mn2+ ions adopt a trigonal-biyramidal (five-coordinate) and octahedral (six-coordinate) environment. Adding K2CO3/Cs2CO3 to the synthesis process is necessary and may act as a mineralizer. Several properties of compounds 1-4 have been characterized in our studies, in particular their strong photocurrent response characteristics under visible light irradiation.